Staging of nutrition disorders in non‐small‐cell lung cancer patients: utility of skeletal muscle mass assessment. Issue 4 (1st April 2019) - Antoun, Sami; Morel, Hugues; Souquet, Pierre‐Jean; Surmont, Veerle; Planchard, David; Bonnetain, Franck; Foucher, Pascal; Egenod, Thomas; Krakowski, Ivan; Gaudin, Hélène; Debieuvre, Didier
Abstract: Background: An international consensus proposed in 2011 a definition and classification system for cachexia (CAX), mainly based on weight loss, sarcopenia [skeletal muscle mass (SMM) loss], inflammation, and anorexia. The aim of this study was to stage CAX in non‐small‐cell lung cancer (NSCLC) patients by using a classification based on the Fearon criteria and supported by quantifiable parameters. Methods: This was a cross‐sectional and non‐interventional multicentre study. SMM was assessed by analysing L3 computed tomography‐scan images. Patients completed the anorexia/CAX subscale of the Functional Assessment of Anorexia/Cachexia Therapy, EORTC QLQ‐C30 quality of life (QoL) and International Physical Activity Questionnaire (IPAQ). Results: Patients were recruited in 56 sites. The analysis population comprised 531 patients, and SMM was assessed in 312 patients. Male patients were 66.5%, with a mean (SD) age of 65.2 (10.0) years, 79.9% were PS 0–1, and the tumour stage was mainly IIIB‐IV (87.3%). Overall, 38.7% of patients had CAX, 33.8% pre‐CAX, and 0.9% refractory CAX. Molecular tumour profiles were significantly associated with the presence of CAX: 23.9% in EGFR, ALK, ROS1, BRAF, or HER2+ patients, 41.4% in K‐RAS+, and 43.2% in patients with no molecular abnormality ( P  = 0.003). The more advanced the CAX stage, the poorer the scores of functional items of the QoL ( P  < 0.001) and International Physical Activity Questionnaire ( P  < 0.001). Sarcopenia was present in 66.7% of CAX and 68.5% of pre‐CAX patients. Overall, 43.8% of pre‐CAX patients had only sarcopenia with limited weight loss (≤2%) and no anorexia. Conclusions: This is the first study to show the distribution of CAX in a population of NSCLC patients and an association between molecular abnormality in NSCLC and CAX. The original Fearon classification for CAX stages was supported by the associated functional QoL scores and physical activity levels, resulting in a clinically relevant system for detection of early stages of CAX.